Peran Singapura dalam ASEAN Agreement on Electronic Commerce (AAEC) - Euis Putri Rahmadhani; Muhammad Yusra (Palito, 2026)
ASEAN Agreement on Electronic Commerce (AAEC) is an agreement in Southeast Asia initiated by Singapore that aims to facilitate cross-border e-commerce cooperation in the region. This research analyzes the role of Singapore in the ASEAN Agreement on Electronic Commerce. The research method used is qualitative with descriptive and exploratory research using primary and secondary data. This research uses National Role Conceptions by K.J. Holsti to analyze the role of Singapore in AAEC. The researchers identify four national role conceptions, such as regional leader, regional-subsystem collaborator, developer, and example. Singapore’s role as a regional leader is evidenced by Singapore leading the e-commerce task force in the region and initiating the AAEC. Role as a regional-subsystem collaborator, Singapore shows a commitment to establishing cooperation between ASEAN member states and aims to achieve common interests through AAEC. Singapore collaborated with Malaysia and Brunei Darussalam in the e-commerce task force. Singapore actively cooperates with other ASEAN member states to implement the area of cooperation in AAEC. Singapore’s role as the developer has developed Singapore Cooperation Centres in Vietnam, Cambodia, and Lao PDR aims to give training and workshops about e-commerce. The role as example, Singapore is a country with the most advanced e-commerce infrastructure in the region and becoming an example for other countries. Singapore inspires other ASEAN member states to support the implementation of AAEC. Keywords: ASEAN Agreement on Electronic Commerce, Southeast Asia, E-Commerce, National Role Conceptions, Singapore.